A non‐isolated high step‐up DC–DC converter using magnetic coupling and voltage multiplier circuit. Issue 9 (2nd May 2021) - Pourjafar, Saeed; Shayeghi, Hossien; Hashemzadeh, Seyed Majid; Sedaghati, Farzad; Maalandish, Mohammad
Abstract: This paper introduces a new DC–DC structure with a high voltage gain. The proposed structure can achieve higher voltage gain by using magnetic coupling and voltage multiplier circuit (VMC). The VMC is also used as a clamp circuit to suppress the voltage spike through the switch which leads to increase the overall system efficiency. Moreover, the peak voltage through the semiconductors of the proposed converter is low. The existence of soft‐switching such as zero‐current switching (ZCS) in OFF‐state and zero‐voltage switching (ZVS) in ON‐state of diodes is another merit of the proposed converter. The recommended structure uses one power MOSFET with low on‐state resistance ( R DS‐ON ) that leads to decrease the conduction loss. For demonstrating the proficiency of the proposed structure, technical analysis, mathematical survey, and comparison results with other similar previous structures are carried out. Finally, laboratory results with 200 W output power and 50 kHz switching frequency are provided, which prove the usefulness of the suggested converter. The proposed converter's efficiency in 200 W output power is 96.98 %. Also, the voltage gain, maximum voltage stress across the power switch and didoes for n (turn‐ratio) = 2 and D (duty‐cycle) = 0.6 are equal to 10, 0.25, and 0.75, respectively.